CABG - Challenging Cases in Apollo Hospitals Dhaka, A Decade of Experience (Pulse, 2017)
Objective: To show outcome of challenging cases of Coronary Artery Bypass Graft (CABO)Methods: A retrospective study, done in Apollo Hospitals Dhaka from 02-05-2005 to 13.12.2014. Total 1892 CABO cases were reviewed- Emergency: 22 cases, Off-pump: 1257 cases, Arrested heart: 554 cases, On-pump beating heart: 81 cases, MIDCAB: 2 cases. Female - 213 (11.25%), male -1679 (88.74%). Associated co-morbities: peripheral vascular disease: 19 cases, COPD: 78 cases, on dialysis: 17 cases, ventricular septal ruptures :10 cases, carotid occlusive disease: 88 cases, old stroke: 58 cases, permanent pacemaker: 4 cases, preoperative ventilator: 29 cases, left ventricular aneurysm: 58 cases, severe mitral regurgitation: 5 cases, EF: 31-50% =260 cases, 21-30% =147 cases, 15- 20% = 8 cases. Associated procedures -left ventricular aneurysm repair: 42 cases, mitral valve replacement: 30 cases, aortic valve replacement: 25 cases ,double valve replacement: 3 cases, RA myxoma removal: 1 case, LV aneurysm repair with mitral valve procedure: 5 cases , LV aneurysm repair with ventricular septal rupture repair: 5 cases, ventricular septal rupture repair: 10 cases, aorto-femoral bypass: 3 cases, ileo femoral bypass: 1 case, left aorto-axillary bypass: 1 case , Bentall procedure with Brachio-cephalic artery re-implantation: 1 case, Aorto-bifemoral bipopliteal bypass: 1 case, redo CABO-7, IABP preoperatively: 12 cases.Results: Overall mortality rate 2.12% (39 cases), emergency 9.09 % (2 cases) mortality, routine mortality 1.97% (37 cases).Conclusion: Challenging cases of CABO can be done with acceptable morbidity and mortality with good long term outcome.Pulse Vol.9 January-December 2016 p.6-14